Whole issue - Language Value (Universitat Jaume I. Department of English Studies, 2018)
Table of Contents From the editors Begoña Bellés-Fortuño Articles  Multimodal literacy in academic environments: PowerPoint as a motivational genre. Stefania Consonni PowerPoint Presentations in the classroom: Re-evaluating the genre. Larissa d'Angelo Listening with your eyes: Multimodal approaches to art appreciation in primary school. Ruth Breeze Teacher's feedback vs. computer-generated feedback: A focus on articles. Tamara Hernández Puertas Book and Multimedia Reviews  Arlene Archer and Esther Odilia Breuer. Multimodality in Higher Education. Lucía Bellés-Calvera